The Persona Shield: How Debate-Based Role-Play Precedes Fluency in an Indonesian Madrasah - Egamberdieva Mohlaroyim; Dwi Fita Heriyawati (Educazione: Journal of Education and Learning, 2025)
Indonesian students study English for years and still fall silent when asked to speak it. Two cultural pressures explain much of this. Malu attaches shame to public error, while Sok Inggris marks a fluent speaker as pretentious. Existing research treats anxiety reduction and fluency improvement as parallel gains from role-play, yet no study has examined how the two are related. This qualitative descriptive study investigated debate-based role-play among 25 Grade XI students at MA Almarif Singosari, a madrasah aliyah in East Java. Data came from classroom observation, written reflection sheets completed by all participants, and semi-structured interviews with seven purposively selected students and their English teacher. Thematic analysis produced four findings. Assigned debate roles displaced students' self-monitoring and reduced hesitation. The persona shifted ownership of error from the student to the character, a mechanism one student described as wearing a shield. Students valued the strategy for its utility, engagement, and communicative autonomy. Vocabulary limits and residual shame nevertheless persisted, with 60 percent naming lexical gaps as their chief difficulty and 24 percent still reporting embarrassment. These findings indicate that anxiety mitigation precedes fluency rather than accompanying it, and that vocabulary is the constraint that survives it. Teachers who address anxiety alone will produce students willing to speak but short of words. Speaking instruction should therefore establish the affective condition first and supply lexical resources before the task, not after it fails.